Konsepsi Fiqh Jinayah dalam Merumuskan Sanksi Hukum Pembunuhan Mutilasi - Ropei, Ahmad (Al-Jinayah : Jurnal Hukum Pidana Islam, 2021)
Among the serious problems facing society is murder accompanied by mutilation. This paper aims to describe the jinayah fiqh conception of mutilation and its legal sanctions. The results of this paper indicate that mutilation is murder which is followed by dismembering the limb of the victim. In positive criminal law, mutilation is charged under Article 340 of the Criminal Code with the threat of alternative sanctions, namely the death penalty or life imprisonment, or for a specified period of up to twenty years. Murder of mutilation in the concept of jinayah fiqh is classified as deliberate killing (qatl al-'amd), this is based on the existence of an element of intentional intention (intention) as a key element for determining the radius of deliberate killing (qatl al-'amd). The punishment formulated for the perpetrator of deliberate murder is qisas, which is the death penalty as retribution for the perpetrator.